Bacterial DUBs: deubiquitination beyond the seven classes. (17th December 2019) - Hermanns, Thomas; Hofmann, Kay
Abstract : Protein ubiquitination is a posttranslational modification that regulates many aspects of cellular life, including proteostasis, vesicular trafficking, DNA repair and NF-κB activation. By directly targeting intracellular bacteria or bacteria-containing vacuoles to the lysosome, ubiquitination is also an important component of cell-autonomous immunity. Not surprisingly, several pathogenic bacteria encode deubiquitinases (DUBs) and use them as secreted effectors that prevent ubiquitination of bacterial components. A systematic overview of known bacterial DUBs, including their cleavage specificities and biological roles, suggests multiple independent acquisition events from host-encoded DUBs and other proteases. The widely used classification of DUBs into seven well-defined families should only be applied to eukaryotic DUBs, since several bacterial DUBs do not follow this classification.